1994
DOI: 10.1080/10408399409527665
|View full text |Cite
|
Sign up to set email alerts
|

Myofibrillar protein from different muscle fiber types: Implications of biochemical and functional properties in meat processing∗

Abstract: Texture, moisture retention, and tenderness of processed muscle foods are influenced by the functionality of myofibrillar protein. Recent studies have revealed large variations in processing quality between red and white muscle groups that can be attributed to differences in the functional properties of myofibrillar protein associated with the type of fiber. Myofibrillar proteins from fast- and slow-twitch fibers exhibit different biochemical and rheological characteristics and form gels with distinctly differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
108
0
5

Year Published

1996
1996
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 165 publications
(119 citation statements)
references
References 124 publications
6
108
0
5
Order By: Relevance
“…The high solubility of protein is thought to only alter the quantity of the effective gelling components, rather than affecting the specific protein bonds in the gel matrix. This hypothesis is supported by the observation that the proteins form substantially weaker gels as the pH is raised from 6.0 to 7.0 (Xiong, 1994). Thus, we propose that the different gel strength of MP-FG induced by pH is ascribed to the protein-protein and protein-FG interactions that form the gel structures with various texture properties.…”
Section: Effects Of Ph On the Gel Strength Of Thermal Mp-fg Gelsupporting
confidence: 67%
“…The high solubility of protein is thought to only alter the quantity of the effective gelling components, rather than affecting the specific protein bonds in the gel matrix. This hypothesis is supported by the observation that the proteins form substantially weaker gels as the pH is raised from 6.0 to 7.0 (Xiong, 1994). Thus, we propose that the different gel strength of MP-FG induced by pH is ascribed to the protein-protein and protein-FG interactions that form the gel structures with various texture properties.…”
Section: Effects Of Ph On the Gel Strength Of Thermal Mp-fg Gelsupporting
confidence: 67%
“…Charged alginate polymers in meat system compete for water to form a viscous sol or visco-elastic gel, thereby interfering with their structure-forming ability and gel matrix formation (Tolstoguzov, 1991;Xiong and Blanchard, 1993). In structured beef, Xiong (1994) reported that addition of connective tissue reduced the stability of beef batters. Sci., 5 (1): 14-48, 2015Hughes et al (1997 found increased emulsion stability in frankfurters formulated with carrageenan and 0.7% carrageenan incorporation resulted in the highest (p<0.05) emulsion stability (as total volume released) compared to 0.5% and controls.…”
Section: Quality Of Restrucutred Meat Products Cooking Yieldmentioning
confidence: 99%
“…It is widely accepted that the myofibrillar proteins are the main responsible for the technological quality of the meat products (Xiong, 1994). Previous works have informed on the physico-chemical, biochemical, and functional properties of major myofibrillar proteins from squid Illexargentinus (Paredi, Roldán, & Crupkin, 2006;Mignino & Paredi, 2006).…”
Section: Introductionmentioning
confidence: 99%